Design of a mini solar power system - Tan, Yu Hee; Mohd Isa, Maryam (IEEE, 2009)
This paper presents the design of mini solar power system. The mini solar power system is designed based on photovoltaic cell generation and 12V direct current system. The main part of the solar power system is the charge controller that is analysed and presented in this paper. The overall system will be constructed for measurement and testing.